Does Corporate Governance Have a Say on Dividends in Australian Listed Companies? - Omar Al Farooque; Ali Hamid; Lan Sun (Australasian Accounting, Business and Finance Journal, 2021)
This paper investigates whether corporate governance has an impact on dividend policy in Australian listed firms. The empirical studies of corporate governance and dividend policy in the Australian context tend to have a limited scope and the findings are mixed. Unlike the existing literature, this paper provides a more comprehensive examination of the relationship between dividend policy and corporate governance mechanisms. Using a sample of 1,438 firm-year observations for the period of 2005 to 2011 and the panel data approach, this study finds that dividend payout is significantly positively (negatively) correlated with board size, board independence, institutional ownership and use of a Big-4 audit firm (CEO duality and managerial ownership). Moreover, dividend yield is significantly positively (negatively) correlated with managerial ownership (foreign ownership). These findings suggest that dividend policy and corporate governance mechanisms are complementary i.e. firms paying higher dividends are more likely to engage in good governance practices as well as having strong monitoring and control systems in place and therefore both dividend policy and corporate governance are considered as effective tools in reducing agency costs.
Keywords: Dividend payout; dividend yield; corporate governance; Australia